THE FACTORS THAT INFLUENCE THE STUDENTS’ DIFFICULTIES IN RETELLING A MOVIE - Dita Anggraini; Destri Wahyuningsih (AL-ISHLAH: Jurnal Pendidikan, 2020)
The objective of this research were to know the factors that influence the students’ difficulties in retelling a movie. The subject of this research consists of 14 students at second semester STKIP Insan Madani Airmolek. The method used in this study was Descriptive Analysis Research. The data of this research was gathered through retelling a movie test and giving questionnaire. The techniques of data analysis used quantitative and qualitative analysis. The quantitative analysis was used to count the percentage of student’s score test and students answer the questionnaire. On the other hand, the qualitative analysis used to describe or interpret the result of quantitative analysis result. The researcher obtained the scores of the test result were 43, 57%. It was categorized less. And then the factors that influence students’ difficulties based on indicators of retelling a movie are English movie media, limited educational background to watch English movie and students’ less practice.The factors that influence difficulties from the internal factor was intelligence got 54%, interest got 78% and fatigue got 3%. The most factors that influence is interest. It got 78% of the students felt uninterested to watch the movie and retell it. The factors that influence difficulties from the external factors were family (56%), school (24%), society (57%). Society factors most influences the students’ difficulties in retelling a movie because the students have more interaction with it. The result of the research showed the factors that influence students’ difficulties occurred because of inappropriate media, students’ bad study habit, students’ point of view, laziness, and bad action negative activities inside and outside them.